Cyber Safe Harbor 4.0: Advancing Ethics and Professionalism in Indo-nesia’s Digital Landscape - Budi Dhaju Parmadi (Green Publisher Indonesia, 2024)
The rapid development of digital platforms has prompted the need for robust policies to ensure ethical and professional conduct among platform and content providers. The